Tracing the criminal women in Edogawa Ranpo’s stories - Kot, Ayşe Selin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Edogawa Ranpo is a Japanese author whose works concentrate on detective fiction. This study focuses on the portrayal of criminal women in his detective fiction works, Appearance of Osei (Osei Tōjō), Beast in the Shadows (Injū), and Caterpillar (Imo Mushi). The study analyses their roles as wives, lovers, and aggressors in their surroundings, and argues that by getting his female protagonists to murder their husbands, Ranpo liberates these women from the social pressure and burden of the patriarchal structures placed on them. To discuss the patriarchal oppression and these women characters’ agency, this research adopts a context-based analysis through the structuration theory. The thesis also argues that by bending the norms of the structures they are restricted in, these criminal characters can be considered as a statement against the ryōsai kenbo (good wife, wise mother) ideology of Meiji Japan.
Keywords: Short stories, Japanese.; Female offenders.